Building envelope retrofits for achieving thermal comfort in naturally ventilated buildings in future climates: A case study of social housing in Egypt - Ebeid, Donna Nader Kamel (AUC Knowledge Fountain, 2023)
Envelope thermal insulation has a significant impact on a scale from global to individual interest. It contributes to indoor thermal comfort, provides economic benefit through reduced electricity bills, increases energy efficiency of buildings through reduced energy consumption, and protects against the change in Earth’s climate through reduced greenhouse gas emissions. In 2021, building operations accounted for 30% of global energy consumption, 27% of annual global CO2 emissions and 35% of building energy use accounted for electricity consumption which is used to create comfortable indoor living conditions. In Egypt, electricity consumption in residential sector has been steadily increasing, among other sectors, in response to climate change projections and the rapid expansion of new communities and housing units. As the mean annual global temperature is expected to increase by 2 to 3°С by 2050, thermal discomfort in residential buildings, that do not have AC installed, is expected to increase. However, increased discomfort may result in residents adding AC to their spaces – which will lead to increased electricity demand and further growth of emissions. Using energy simulations (designbuilder software), this research studies a case of typical social housing units, which currently don’t have AC installed, to investigate thermal discomfort using A2 emission scenario based on ASHRAE 55 adaptive comfort model. The research compares the number of discomfort hours in three climate zones in Egypt (Cairo, Alexandria, and Aswan), under the current and projected weather in 2050 and 2080 using proposed retrofitting options to the existing envelope wall section. While previous studies have investigated the impact of envelope insulation on thermal comfort based on whole-building simulations, this research focuses specifically on the analysis of occupancy schedule and comfort in different spaces (dining & reception vs bedroom) which is novel and highlights the need for investigating possible space by space retrofits to improve thermal comfort of each space. Generally, envelope insulation doesn’t result in a significant reduction in discomfort hours in naturally ventilated buildings. However, research findings showed that zones occupied during minimum temperatures (such as bedrooms), without thermal insulation, will suffer from discomfort due to heat loss leading to increased electricity consumption for heating.